Influence of selected dietary components on the functioning of the human nervous system - Agnieszka Wendołowicz; Ewa Stefańska; Lucyna Ostrowska (National Institute of Public Health - National Institute of Hygiene, 2018)
The diet is directly connected not only with the physical status but also with the functioning of the brain and the mental status. The potentially beneficial nutrients with a protective effect on the nervous system function include amino acids (tryptophan, phenylalanine, tyrosine, taurine), glucose and vitamins C, E, D and beta-carotene, B group vitamins (vitamin B12, vitamin B6, vitamin B4, vitamin B1) and minerals (selenium, zinc, magnesium, sodium, iron, copper, manganese, iodine). The presence of antioxidants in the diet protects against oxidative damage to nervous system cells. Biochemical data indicate that polyunsaturated fatty acids such as arachidonic acid (AA), docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and gamma-linolenic acid (GLA) as structural components of the nervous system play a key role in its function. The nutrition of the entire body also influences the production of neurotransmitters in the brain. A diet without an appropriate supply of protein, mineral nutrients or vitamins may result in a failure to form appropriately balanced numbers of neurotransmitters, which, as a result, may lead to neurotransmission dysfunction. This is the reason why proper nutrition is based on vegetables, fruits, whole-grain cereal products supplemented with products providing full-value protein (dairy products, fish, lean meat) and high-quality fat products (vegetable oils, fish fats).